Influential factors that contribute to consumers’ choice of children’s underwear in an effort to alleviate sensory overreactivity - Diedericks, Lizette (University of Pretoria, 2024)
Dissertation (MSc (Consumer Science: Clothing Management))--University of Pretoria, 2023.